Reticular Epithelial Edema: An Uncommon Side Effect of ROCK/NET Inhibitor Netarsudil. Issue 11 (November 2020) - Chen, Hongan; McMillin, Jake C.; Frankfort, Benjamin J.; Al-Mohtaseb, Zaina
Abstract : A 66-year-old female with advanced primary open-angle glaucoma and Descemet's stripping endothelial keratoplasty OD with previously noted inferior stromal edema presented with a 1-month history of progressive decreased visual acuity after starting netarsudil twice daily. Her best-corrected visual acuity was 20/80 OD and no light perception OS. The right cornea was notable for inferior small epithelial bullae in a reticular pattern from 2 to 9 o'clock encroaching on the visual axis involving both sides of the graft-host junction. The reticular epithelial edema resolved upon discontinuation of netarsudil and best-corrected visual acuity improved to 20/50 but was limited by persistent stromal edema. We report a patient with a history of a partially decompensated Descemet's stripping endothelial keratoplasty who develops reticular epithelial corneal edema after starting netarsudil. This unique pattern of edema may present in the setting of preexisting endothelial cell dysfunction when netarsudil is used, a complication not noted in the Food and Drug Administration (FDA) trials.